Who shall pay for the public good? Comparative trends in the funding crisis of public higher education - Kwiek, Marek; Lebeau, Yann; Brown, Roger (My University, 2012)
Polish higher education is one of the most heavily marketised systems in Europe, due to its extraordinarily high share of fee-paying students and the highest share of enrolments (and student numbers) in a private sector in Europe (0.58 million students out of 1.82 million in 2010). Expected demographics may fundamentally change the educational setting in the country, though: it may lead to the re-monopolisation of the system by the public sector, which was unthinkable a decade ago.
Keywords: public good; private good; cost-sharing; higher education; Poland; Europe; private sector; fees and loans; public policy; reforms; privatization; demographic decline